2017
DOI: 10.3390/buildings7010013
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Thermal Insulation in Lightweight Steel-Framed Walls with Respect to Its Position

Abstract: Lightweight steel-framed (LSF) construction, given its advantages, has the potential to reach high standards in energy and environmental performance of buildings, such as nearly zero-energy buildings (nZEB). When compared with traditional construction, LSF system offers distinct benefits in such fields as sustainability, cost-effectiveness, constructive process, and safety at work. Despite the benefits of this constructive system, the effect of thermal bridges in LSF elements, caused by the high thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 20 publications
0
66
0
2
Order By: Relevance
“…Their relevance to the overall U-value of LSF wall is also low, as previously verified in refs. [9] [27]. Moreover, given the very reduced thickness of the vapour barrier (about 0.2 mm) and its consequent negligible influence in wall U-value, it was adopted not to use it in the experimental lab tests, neither in the numerical simulations.…”
Section: Walls Description and Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their relevance to the overall U-value of LSF wall is also low, as previously verified in refs. [9] [27]. Moreover, given the very reduced thickness of the vapour barrier (about 0.2 mm) and its consequent negligible influence in wall U-value, it was adopted not to use it in the experimental lab tests, neither in the numerical simulations.…”
Section: Walls Description and Materials Characterizationmentioning
confidence: 99%
“…Thermal bridging originated by steel studs is seen as a hot topic of research in the LSF construction research field. Roque and Santos [9] studied the effectiveness of thermal insulation in LSF walls regarding its position in the assemblage. They concluded that external thermal insulation is more effective than batt insulation.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the batt insulation, besides the thermal insulation function, can also perform an important acoustic insulation function [4]. Moreover, the effectiveness of thermal insulation depends on its position in the LSF element [5], as well as on the type of LSF construction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations could be performed with more simpler two-dimensional (2D) models [5,6] or more complex/detailed three-dimensional (3D) models [9,10]. They have the advantage of allowing a quick comparison between several building component solutions/configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The space between the studs can be filled with mineral wool which additionally improves thermal insulation of the interior and can serve as a soundproofing layer. It should be noted that linear thermal bridges can be formed near the locations of steel sections of the framing [2,3].…”
Section: Introductionmentioning
confidence: 99%